Dysregulation of interferon regulatory factors impairs the expression of immunostimulatory molecules in hepatitis C virus genotype 1-infected hepatocytes. Issue 4 (20th June 2013) - Larrea, Esther; Riezu-Boj, Jose-I; Aldabe, Rafael; Guembe, Laura; Echeverria, Itziar; Balasiddaiah, Anangi; Gastaminza, Pablo; Civeira, María Pilar; Sarobe, Pablo; Prieto, Jesus
Abstract : Background: IL-7 and IL-15 are produced by hepatocytes and are critical for the expansion and function of CD8 T cells. IL-15 needs to be presented by IL-15Rα for efficient stimulation of CD8 T cells. Methods: We analysed the hepatic levels of IL-7, IL-15, IL-15Rα and interferon regulatory factors (IRF) in patients with chronic hepatitis C (CHC) (78% genotype 1) and the role of IRF1 and IRF2 on IL-7 and IL-15Rα expression in Huh7 cells with or without hepatitis C virus (HCV) replicon. Results: Hepatic expression of both IL-7 and IL-15Rα, but not of IL-15, was reduced in CHC. These patients exhibited decreased hepatic IRF2 messenger RNA levels and diminished IRF2 staining in hepatocyte nuclei. We found that IRF2 controls basal expression of both IL-7 and IL-15Rα in Huh7 cells. IRF2, but not IRF1, is downregulated in cells with HCV genotype 1b replicon and this was accompanied by decreased expression of IL-7 and IL-15Rα, a defect reversed by overexpressing IRF2. Treating Huh7 cells with IFNα plus oncostatin M increased IL-7 and IL-15Rα mRNA more intensely than either cytokine alone. This effect was mediated by strong upregulation of IRF1 triggered by the combined treatment. Induction of IRF1, IL-7 and IL-15Rα by IFNα plus oncostatin M was dampened in replicon cells but the combination was more effective than either cytokine alone. Conclusions: HCV genotype 1 infection downregulates IRF2 in hepatocytes attenuating hepatocellular expression of IL-7 and IL-15Rα. Our data reveal a new mechanism by which HCV abrogates specific T-cell responses and point to a novel therapeutic approach to stimulate anti-HCV immunity.